2014
DOI: 10.1007/s00467-014-2821-8
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria correlates with hemolysis and NAG and KIM-1 in patients with sickle cell anemia

Abstract: Despite a normal or increased eGFR, KI biomarkers were detected in the urine of individuals with SCA. NAG, KIM-1 and urine hemosiderin correlated with the presence of albuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…20,[52][53][54][55][56][57] KIM-1 is a transmembrane protein whose expression and release by proximal tubular cells is increased after exposure to inflammatory stimuli. 58 Consistent with other studies, 59,60 we observed that concentrations of urine KIM-1 were increased in SCD patients with albuminuria. A unique finding of our study is that KIM-1 concentration significantly correlated with cell-free hemoglobin concentration in the urine of patients with SCD and in the supernatant of HK-2 cells exposed to cell-free hemoglobin.…”
Section: Discussionsupporting
confidence: 91%
“…20,[52][53][54][55][56][57] KIM-1 is a transmembrane protein whose expression and release by proximal tubular cells is increased after exposure to inflammatory stimuli. 58 Consistent with other studies, 59,60 we observed that concentrations of urine KIM-1 were increased in SCD patients with albuminuria. A unique finding of our study is that KIM-1 concentration significantly correlated with cell-free hemoglobin concentration in the urine of patients with SCD and in the supernatant of HK-2 cells exposed to cell-free hemoglobin.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, intravascular hemolysis represents an intrinsic mechanism for human vascular disease that manifests clinical complications in sickle cell disease and other chronic hereditary or acquired hemolytic anemias. (24)(25)(26). In contrast, as mentioned earlier, other complications were associated with lower hemolysis rates and higher steady-state hemoglobin levels, including the rate of vaso-occlusive painful episodes, ACS, and osteonecrosis (Table 1).…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, hemoglobin dimers released during hemolysis promote albuminuria by inhibiting the reuptake of albumin in the proximal tubule [56]. Levels of albuminuria in SCN also correlate with hemolysis and markers of tubular injury [24].…”
Section: Hematuriamentioning
confidence: 99%
“…Risk factors that have been associated with the development of pediatric SCN are older age, early severe anemia, severe hemolysis, Central African Republic sickle haplotype, elevated blood pressure for age, priapism, and hyperuricemia [1,13,17,[19][20][21][22][23][24].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation